(untitled) (Docentes 2.0 Journal, 2022)
Innovation is an important term in the educational process. In the pandemic, technology has been a crucial element in education; technological resources have promised to stimulate education that benefits pedagogical continuity. The research objective allowed the application of educational resources based on gamification as an innovative method for meaningful student learning. For the development of this research, the observation method was used a positivist paradigm, a quantitative approach, a correlational type, and a quasi-experimental design. It had the participation of 33 students from the Technical University of Machala, Experimental Sciences Career for its development, and data collection techniques based on the Likert scale were applied that allowed the collection of information by the actors and instruments. As a result, it was obtained that 85% indicated that the gamification elements were easy to use, 91% said that the strategies used in the development of virtual classes allowed the understanding of all the contents established in the syllabus, and 100% considered that the resources used were exciting. Finally, it can corroborate that educational innovation has contributed significantly to the development of students’ skills by using different digital elements such as educational resources with elementary characteristics that allow pedagogical transformation.